Rome Foundation-Asian working team report: Asian functional gastrointestinal disorder symptom clusters. Issue 6 (7th June 2017) - Siah, Kewin Tien Ho; Gong, Xiaorong; Yang, Xi Jessie; Whitehead, William E; Chen, Minhu; Hou, Xiaohua; Pratap, Nitesh; Ghoshal, Uday C; Syam, Ari F; Abdullah, Murdani; Choi, Myung-Gyu; Bak, Young-Tae; et al.
Abstract : Objective: Functional gastrointestinal disorders (FGIDs) are diagnosed by the presence of a characteristic set of symptoms. However, the current criteria-based diagnostic approach is to some extent subjective and largely derived from observations in English-speaking Western patients. We aimed to identify latent symptom clusters in Asian patients with FGID. Design: 1805 consecutive unselected patients with FGID who presented for primary or secondary care to 11 centres across Asia completed a cultural and linguistic adaptation of the Rome III Diagnostic Questionnaire that was translated to the local languages. Principal components factor analysis with varimax rotation was used to identify symptom clusters. Results: Nine symptom clusters were identified, consisting of two oesophageal factors (F6: globus, odynophagia and dysphagia; F9: chest pain and heartburn), two gastroduodenal factors (F5: bloating, fullness, belching and flatulence; F8 regurgitation, nausea and vomiting), three bowel factors (F2: abdominal pain and diarrhoea; F3: meal-related bowel symptoms; F7: upper abdominal pain and constipation) and two anorectal factors (F1: anorectal pain and constipation; F4: diarrhoea, urgency and incontinence). Conclusion: We found that the broad categorisation used both in clinical practice and in the Rome system, that is, broad anatomical divisions, and certain diagnoses with long historical records, that is, IBS with diarrhoea, and chronic constipation, are still valid in our Asian societies. In addition, we found a bowel symptom cluster with meal trigger and a gas cluster that suggests a different emphasis in our populations. Future studies to compare a non-Asian cohort and to match to putative pathophysiology will help to verify our findings.